Is "Not Trading" Informative? Evidence from Corporate Insiders' Portfolios. Issue 1 (2nd January 2022) - DeVault, Luke; Cederburg, Scott; Wang, Kainan
Abstract: Some individuals, e.g., those holding multiple directorships, are insiders at multiple firms. When they execute an insider trade at one firm, they may reveal information about the value of all—both the traded insider position and not-traded insider position(s)—the securities held in their "insider portfolio." We find that insider "not-sold" stocks outperform "not-bought" stocks. Implementable trading strategies that buy not-sold stocks following the disclosure of a sale earn alphas up to 4.8% per year after trading costs. The results suggest that even insider sales that are motivated by liquidity and diversification needs can provide value-relevant information about insider holdings.